Microsoft Excel 2000 complete tutorial - Cable, Sandra; Pasewark, William R. (Cincinnati : South-Western Educational, 2000)
This book presents about Microsoft Excel and its applications.
Keywords: Business; Computer programs; Microsoft Excel for Windows; Microsoft Excel for Windows; Business -- Computer programs; Electronic spreadsheets